Pembangunan Berkelanjutan melalui Green Economy Perspektif Maqashid Syariah - Ciptia Khoirulina Sanawati; Rizky Selvia Putri (Institut Agama Islam Negeri Ponorogo, 2025)
This study examines integrating green economy principles with Maqashid syariah (Islamic law's higher objectives) as a sustainable development framework in Indonesia. Using qualitative library research and content analysis methods, the research explores how Islamic economic concepts such as khalifah (stewardship), mizan (balance), and prohibition of israf (wastefulness) align with contemporary green economy approaches. The findings reveal that Maqashid syariah's five essential protections (religion, life, intellect, progeny, and wealth) provide a comprehensive ethical foundation for sustainable development that complements the United Nations' green economy model. The study highlights Indonesia's initiatives in green Islamic finance, particularly green sukuk, while identifying implementation challenges, including policy gaps and limited public awareness. The research contributes to Islamic economics literature by proposing an integrative model that combines environmental sustainability with Islamic values, offering practical recommendations for policymakers and Islamic financial institutions to advance sustainable development goals.